The Accountability Paradox in Hybrid Zakat Governance: Evidence from BAZNAS Kota Yogyakarta - Savira Nur Aini; Sudarmo; Faizatul Ansoriyah (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2026)
Contemporary public accountability reforms often assume that stronger transparency, auditability, and regulatory compliance will enhance organizational legitimacy and strengthen public trust. This assumption remains contested, particularly in hybrid faith-based public organizations that operate under overlapping bureaucratic and moral-religious accountability demands. This study examines public accountability practices in BAZNAS Kota Yogyakarta as a local zakat governance institution with strong formal compliance structures. Using a qualitative case study approach, data were collected through document analysis, semi-structured interviews, and non-participant observation. The analysis applies a multidimensional public accountability framework encompassing legal, financial, managerial, and social accountability, interpreted through the lenses of symbolic transparency and institutional decoupling. Findings show that BAZNAS Kota Yogyakarta demonstrates strong formal accountability through regulatory compliance, layered audit systems, standardized reporting, and active digital disclosure. Substantive accountability, however, remains comparatively limited. Managerial accountability is primarily oriented toward program delivery rather than systematic outcome evaluation, while social accountability is characterized more by informational openness than meaningful participatory engagement. These patterns suggest an accountability paradox in which visible compliance strengthens formal legitimacy without fully translating into substantive accountability. The study argues that accountability in hybrid faith-based public organizations should not be understood solely as a technocratic compliance mechanism, but as a contested governance process shaped by competing institutional logics, public expectations, and organizational legitimacy pressures. The findings contribute to public administration scholarship by extending accountability debates into the context of hybrid zakat governance.